The Use Of Video Tutorial In Teaching Writing Procedure Text At Seventh Grade Of SMP Negeri 1 Pematang Siantar - Elisabeth Sinaga; Yanti kristina Sinaga; Basar Lolo Siahaan (CV Putra Publisher, 2023)
The aim of this research was to obtain the empirical evidence about the effect of using video tutorial in teaching writing procedure text at seventh grade of SMP Negeri 1 Pematang Siantar. The method used in this research was a quantitative method and the research design was a quasi – experimental. The sample of the research was seventh grade students of SMP Negeri 1 Pematang Siantar. They were VII-9 as the experimental class and VII-11 as control class. Each class consisted of 30 students which was selected by purposive sampling technique. The experimental class was taught by using Video Tutorial while in the control class was taught without Video tutorial. Data collection instruments used writing tests for pre-test and post-test, Jacob et al writing assessment rubric was used in this research, which includes two aspects : content and organization. The result obtained from this research showed it was proven from the mean score of the post-test of students in experimental class was 79,56 and the mean score of pre-test was 49,36 that were taught by using video tutorial which was improved better than the control class, pre-test in the control class was 60,63 and post-test in the control class was 71,73. Moreover, the result of the t-test calculation was 2,865 which is higher than that T count < T table where T count was 2,865 and T table for df 58 = 1,672 ( 2,865 > 1,672) than Hypothesis Alternative (Ha) accepted and Null Hypothesis (H0) was rejected. Thus, the use of Video Tutorial gives significant effect in teaching writing Procedure Text at seventh grade of SMP Negeri 1 Pematang Siantar.